A Real Time Condition Monitoring System for Gears Operating under Variable Load Conditions - Abdullah Alwadie (Institute of Advanced Engineering and Science, 2018)
Gears are important component of the rotational power transmission system and are largely used in variable load and speed applications. The faults on the gear generate excessive vibration which leads to breakdown of the machine. Sensor based methods could diagnose gear faults but proved to be expensive and have limited applications due to heavy cost and need of access of gear box for sensor installation. The motor stator current analysis has been reported to overcome the drawbacks of the sensor based fault detection methods. However, motor stator current analysis has a limited capability for reliable detection of small gear fault signatures typically for low load conditions. This paper presents an alternative non-invasive approach based on instantaneous power analysis of the motor to reliably diagnose gear faults for variable load applications. The theoretical and experimental results indicates that the instantaneous power analysis offers three fault related harmonics and amplitude variations on these harmonics could give the indication of health status of the gear. The superiority of the proposed instantaneous power analysis technique has been confirmed through experiments performed on three operating points of the motor. The comparison of the amplitude sensitivity of the motor stator current and instantaneous power at three operating points has been performed to validate the superiority of the proposed technique.